2018
DOI: 10.1371/journal.ppat.1007179
|View full text |Cite
|
Sign up to set email alerts
|

A cancer-associated Epstein-Barr virus BZLF1 promoter variant enhances lytic infection

Abstract: Latent Epstein-Barr virus (EBV) infection contributes to both B-cell and epithelial-cell malignancies. However, whether lytic EBV infection also contributes to tumors is unclear, although the association between malaria infection and Burkitt lymphomas (BLs) may involve excessive lytic EBV replication. A particular variant of the viral promoter (Zp) that controls lytic EBV reactivation is over-represented, relative to its frequency in non-malignant tissue, in EBV-positive nasopharyngeal carcinomas and AIDS-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 93 publications
(99 reference statements)
1
70
0
Order By: Relevance
“…Moreover, a large-scale prospective study in Taiwan showed that patients that had antibodies to at least one of two lytic proteins were at least four times more likely to develop nasopharyngeal carcinoma than seronegative patients [93]. Direct evidence of the importance of lytic reactivation in EBV tumors was recently provided by a study examining a naturally occurring polymorphism in the promoter of the EBV BZLF1 protein, which controls the latent-to-lytic switch of the virus [94]. This polymorphism is over-represented in the EBV sequences isolated from tumor tissues of patients with EBV-associated nasopharyngeal carcinoma, AIDS-associated lymphomas, Burkitt’s lymphomas and gastric carcinomas [94].…”
Section: Cases In Which Viral Replication Is Required For Oncogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a large-scale prospective study in Taiwan showed that patients that had antibodies to at least one of two lytic proteins were at least four times more likely to develop nasopharyngeal carcinoma than seronegative patients [93]. Direct evidence of the importance of lytic reactivation in EBV tumors was recently provided by a study examining a naturally occurring polymorphism in the promoter of the EBV BZLF1 protein, which controls the latent-to-lytic switch of the virus [94]. This polymorphism is over-represented in the EBV sequences isolated from tumor tissues of patients with EBV-associated nasopharyngeal carcinoma, AIDS-associated lymphomas, Burkitt’s lymphomas and gastric carcinomas [94].…”
Section: Cases In Which Viral Replication Is Required For Oncogenesismentioning
confidence: 99%
“…Direct evidence of the importance of lytic reactivation in EBV tumors was recently provided by a study examining a naturally occurring polymorphism in the promoter of the EBV BZLF1 protein, which controls the latent-to-lytic switch of the virus [94]. This polymorphism is over-represented in the EBV sequences isolated from tumor tissues of patients with EBV-associated nasopharyngeal carcinoma, AIDS-associated lymphomas, Burkitt’s lymphomas and gastric carcinomas [94]. Interestingly, this cancer-associated polymorphism leads to increased BZLF1 expression in response to reactivation stimuli such as B cell receptor activation and, consequently, increased lytic reactivation [94].…”
Section: Cases In Which Viral Replication Is Required For Oncogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Research interest has focused on a viral BZLF1 gene, a master regulator of viral lytic replication . BZLF1 is highly polymorphic both for its coding sequence and promoter region …”
Section: Ebv Genome Heterogeneitymentioning
confidence: 99%
“…One hypothesis is that NPC‐associated EBV strains or subtypes are functionally different from lymphoma‐derived strains. Recent studies have found sequence differences in the EBV genome in NPC in the promoter region driving expression of the BamHIZ leftward frame 1 (BZLF1) [10], the immediate early protein responsible for the switch from latent to lytic infection, and in the Epstein‐Barr virus nuclear antigen 1 (EBNA1) protein [11], both of which appear to promote EBV replication. These observations are consistent with those from a study on an NPC‐derived EBV strain (M81), which was found to be more lytic and to have enhanced tropism for epithelial cells [12].…”
mentioning
confidence: 99%